The criminalisation and exploitation of irregular Chinese migrant workers in the United Kingdom - Luo, Siyu (European journal of criminology, 2023)
This article draws on narrative interviews with irregular Chinese migrant workers (ICMWs) in the United Kingdom (UK) to show how the UK's immigration policies foster forms of illegal working and labour exploitation that they are supposed to combat. It argues that the binary conceptualisation of ?forced labour? as the polar opposite of ?free labour? leaves those migrants working without a right to do so at the risk of both criminalisation and exploitation. The article shows how the fear of criminalisation, together with the pressure to become economically successful in the West, among ICMWs diminishes their capacity to leave exploitative work, reinforcing the unequal power relations between them and their employers, landlords, advisers, and translators. Many ICMWs who are officially cast as ?illegal immigrants? need protection, not from ?snakeheads? and ?traffickers?, but the exploitative and precarious work UK government policies render them economically reliant upon.